Compositional, Sensory and Quality Parameters of Chicken Patties Prepared with Carrots - Patel, Vaibhavi V.; Nayak, Jitendrakumar B.; Bhavsar, Prakrutik P.; Anjaria, Pranav A.; Brahmbhatt, Manoj N.; Parmar, Bhupendrakumar C.; Chaudhary, Jeetendrakumar H.; Soni, Manasi M. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A study was undertaken to determine the effect of the incorporation of grated carrot in chicken patties. Chicken patties were prepared by replacing lean meat with grated carrot at 3 levels, i.e., 10, 15, 20 %. The three treatments along with control were evaluated for physico chemical properties, sensory evaluation and β-carotene estimation. Each experiment was repeated four times. There was a significant increase (P<0.05) in cooking yield, moisture, crude fibre and ash content with an increasing level of grated carrot incorporation. Product pH, crude protein and crude fat showed a significant decrease (P<0.05) with an increase in the level of incorporation of grated carrot. Mean sensory scores for treatments were found to be significantly higher (P<0.05) for texture and overall acceptability, while general appearance was similar when compared to control. The optimum incorporation level of grated carrot was found to be 15 % for chicken patties preparation. Mean sensory scores of 15% grated carrot treatment for general appearance, flavour, texture, juiciness and overall acceptability were comparable with control treatment during the storage period. Chicken patties could be stored safely in LDPE pouches for 9 days at refrigeration temperature (4±1°C).